Secondary School Students' Entrepreneurial Education and Mathematical Problem-Solving Abilities: A Preventive Measure Against Unemployment - Salami, Olajumoke Olayemi; Spangenberg, Erica Dorethea (Mathematics Education Journal, 2025)
This study investigated problem solving skills and entrepreneurship education among secondary school students: an antidote for unemployment in Kwara State, Nigeria. The study was conducted in Ilorin Educational Zone of Kwara State. It was guided by three research question and one hypothesis. The survey research design was adopted. The population of the study covers mathematics students of both public and private secondary schools in the zone. 80 students (35 male and 45 female) were selected using the simple random sampling as sample for the study. One instrument tagged Opinion on Problem Solving Skills and Entrepreneurship Education Questionnaire (OPSEEQ) was used to collect data. OPSEEQ was validated and had a reliability of 0.86 when subjected to the split-half method. The research questions were answered using the mean and standard deviation score while the hypothesis was analyzed using the Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. The result revealed that there was a significant relationship between problem solving skills and entrepreneurship education among students. It was concluded that problem solving skill enhances entrepreneurship education skill. Based on the findings, it was recommended that teachers should encourage students in problem solving skills and teachers of entrepreneurship education should be trained in problem solving to enhance their teaching.